EVALUATION OF CORONAL SHOCK WAVE VELOCITIES FROM THE II TYPE RADIO BURSTS PARAMETERS - Galanin, V. V.; Isaeva, E. A.; Kravetz, R. O. (Одеські астрономічні публікації, 2016)
The work presents the results of research of connection between the coronal shock waves and the parameters of type II (mII) meter-decameter bursts in 25- 180 MHz band for 66 solar proton events. The velocities of coronal shock waves for this two cases where determined. In the first case the velocities of the shock waves was evaluated according to the Newkirck model and in the second case – directly from the type II radio burst parameters. The calculated values of shock waves velocity was compared with the same velocity values that is published on NGDC site. The comparative analysis showed that precision of coronal shock waves velocity estimation which gets directly from type II radio bursts parameters was higher than the same one which used the Newkirck model. Research showed that there is exist the sufficiently strong connection between the shock wave velocity and the delay of type II burst intensity maximum on the second harmonica. Correlation coefficient between the studied parameters was equal to ≈ 0.65.